Autonomy or organisation? Reforms in the Ghanaian internal revenue service - Joshi, Anuradha; Ayee, Joseph (2009)
Autonomous Revenue Authorities (ARAs) have recently become a popular organisational reform to improve revenue collection in developing countries. The success of ARAs is commonly attributed to `autonomy' which reduces political interference, and increases financial independence and managerial freedom. This article examines the case of the Ghanaian ARA - the Internal Revenue Service and argues that its strong performance is the result of not `autonomy', but other more nuts and bolts reforms, specifically: (a) strategies designed to direct the focus of the IRS to different taxpayer segments, particularly the informal sector and (b) significant attempts to bring the tax administration closer to the taxpayer through decentralisation and improved taxpayer services. To the extent that autonomy enables ARAs to undertake these other reforms it forms an important piece of the picture, however, they do not require autonomy - they could well be adopted under traditional tax administrations. - Reproduced.
Keywords: Public finance